IMPROVING STUDENTS’ WRITING ABILITY OF THE ECONOMIC MANAGEMENT STUDY PROGRAM THROUGH BLOGS AT INDO GLOBAL MANDIRI UNIVERSITY PALEMBANG - Desi Surayatika (Universitas Indo Global Mandiri, 2016)
The aims of this study were to find out theprogress in students’ writing achievement after they were taught by using blogs, and to find out the significant difference in students’ writing achievement between the students who were taught by using blogs and those who were not. A quasi-experimental method was used in this study. The population of the study was all the students in Faculty of Economic at Indo Global Mandiri University in the academic year 2014/2015. The sample consisted of 40 students where 20 students for experimental group and 20 students for control group, and was selected by using purposive sampling. In order to get the data, a test was used. The data was obtained in the form of writing test. The test was given twice, to the experimental and control groups, as pre-test and post-test. The result of the test was analyzed by using t-test through SPSS program. The finding showed that (1) There were some progresses in students’ writing due to the use of blog during the teaching and learning activities, and (2) There was a significant difference between the students who were taught by using blogs and those who were not. Key Words: Improving, Writing Ability, Blogs